Steel structures in interaction with non-metallic membranes. Issue 3 (3rd April 2017) - Machacek, Josef; Jermoljev, David
Abstract: Behaviour of prestressed textile membranes supported by peripheral non-rigid steel structures and used for various simple temporary and permanent canopies/shelters is described. The investigation relates to structures composed of membranes located between steel arches only. The approaches for global analysis of the structural system and influence of important parameters such as the membrane prestressing and rigidity of the supporting steelwork are discussed. Extensive parametric study concerning possibility of simplified separate analyses of the membranes and supporting steel structures is presented, giving limiting parameters for such approach. Finally, some recommendations for the analysis and realization of prestressed non-metallic membranes and respective steel supporting structures are provided.